FENOMENA INTRUSI AIR LAUT DI ESTUARI AKIBAT PENGARUH TINGGI PASANG AIR LAUT DENGAN DEBIT HULU SUNGAI MENGGUNAKAN PENDEKATAN MODEL FISIK - Imam Suprayogi (Purifikasi, 2006)
The main purpose of this research is to describe a correlation pattern between laboratory physical model design, mixing parameter and estuary type of the intrusion phenomena in estuary during the dry season. The main result of this research, according to laboratory physical model test was classified as stratified estuary type, with mixing parameter approaching one. This laboratory result was verified to former field research conducted in Kali Porong estuary in 2000. Determination of river flow characteristic at the estuary was done by simulating constant discharge of 10 - 100 m3/detik at the highest annual spring tide during the dry season. One dimension mathematical model approach of the Duflow software version 2.04, was applied. The result showed that there was dominant influence of tide to the upper river. Application of estuarine number (E) equation of Canter Cramer, Kali Porong estuary was classified as stratified estuary.